Meningkatkan Hasil Belajar Matematika melalui Pembelajaran Model Problem Posing Siswa Kelas X TKJ SMK Negeri 1 Tembilahan Tahun 2018 - Sitie Chairhany (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2020)
The Learning Model is one of the supporting factors in teaching mathematics. In choosing one of the teaching methods it will affect the type of learning method that is appropriate, although there are still various other aspects that must be considered in choosing a method including: learning objectives, types of tasks and responses that students are expected to master after learning takes place Problem Posing is a learning method that can increase student activity. It is hoped that students can develop critical and creative thinking skills to build positive attitudes and increase quality human resources in facing a future that is more challenging. Learning problem posing models can be interpreted as the formation of questions to make them simpler and understandable. From the results of the study on the discussion of eating, it can be concluded that theapplication of problem posing model learning can improve mathematics learning outcomes for students in class X-TKJ-1 SMK Negeri 1 Tembilahan 2018 with the subject matter of rank numbers, root forms and logarithms. Periclus learning outcomes before experiencing improvement so that students can achieve mastery in learning. Student completeness in learning cycle 1 was 71.6%, cycle II was 79.7% and cycle III was 95.9%.